Attribution analysis of water-sediment variation under the influence of climate change and human activities in the Kuye River Basin - Jiankang ZHANG; Jiping WANG; Jiansheng SHI (Shuiwen dizhi gongcheng dizhi)
The attribution of the evolution of water and sediment in a river basin is an important theoretical issue in hydrogeology. To understand the change patterns of water and sediment in the Kuye River Basin and provide scientific basis for water resources management and ecological protection under the impacts of climate change and human activities, based on hydrological and meteorological observation data, NDVI (normalized difference vegetation index), and land use change data, this study quantitatively analyzed the trends of water and sediment changes in the basin and their attributed influences using the Mann-Kendall non-parametric test, double mass curve method, cumulative anomaly analysis, sliding rank-sum test, and cumulative quantity slope change rate analysis. The results indicate that from 1956 to 2019, the annual runoff and sediment yield in the Kuye River Basin showed a significant decreasing trend, with an average annual decrease of approximately 10.4 million m3 and 2.7 million tons. The abrupt change year was 1997, verified by the 95% significance level test. From 1998 to 2011, the contribution rates of climate change and human activities to the decrease in annual runoff were 36.06% and 63.94%, respectively. The contribution rates to the decrease in sediment transport were 26.11% and 73.89%, respectively. The decrease in runoff is mainly related to vegetation and land use/cover changes caused by the Grain for Green Program. Using 1998—2011 as the base period, the cumulative slope change rate of runoff reached 109% during 2012—2019. It indicates a significant rebound in runoff, possibly related to the overflow of mine sealing water. The cumulative slope of sediment yield approached 0, indicating no significant change in sediment yield and effective control of soil erosion in the study area. The analysis method of slope change rate of cumulative quantity has good applicability and provides scientific basis for hydrological prediction and management in the Kuye River basin. In the future. It is necessary to pay more attention to the combined effects of ecological restoration and coal mining activities on water resources change.